Relação entre aleitamento, hábitos de sucção, aspectos socioeconômicos e funções estomatognáticas - Neu, Aline Prade (2012)
The importance of breastfeeding has been emphasized because of its benefits in relation to children s development, and also related to the great influence to the development of the stomatognathic system. So, this study has the purpose to verify the relationship between breastfeeding and sucking habits, socioeconomic aspects and the stomatognathic system. As a procedure, parents of 195 children (male and female) answered a questionnaire. The children were aged between 5:0 and 8:11 and attended public and private schools. The collected data were related to type and duration of breastfeeding, respiratory aspects of children, family s socioeconomic, family s monthly income, and mothers education status. Besides, it was investigated the presence and duration of sucking habits. Of the questionnaires, 76 children were randomly assigned to be clinically evaluated. The evaluation was based on the Protocol of Orofacial Myofunctional Evaluation with Scores Expanded Adapted and analyzed the functions of chewing, swallowing and breathing. The speech function was evaluated through the articulatory examination, based on the protocol created at the Speech Therapy Service of Federal University of Santa Maria. The data were analyzed in a descriptive and statistical way, this by means of Chi-Square Test with a level of significance of 5%. The results of the questionnaires showed a predominance of mixed type, but may be noted that exclusive breastfeeding was higher than the exclusive use of the artificial, which is used in addition to two. There was relationship between type of breastfeeding and pacifier habit (p=0,000) and its duration (p=0,000); duration of breastfeeding and pacifier habit (p=0,000) and its duration (p=0,000); artificial breastfeeding, pacifier habit (p=0,000) and its duration (p=0,000). In respect to the socioeconomic aspects, there was relationship between type of breastfeeding and family income (p=0,002). It was possible to conclude that the type and duration of breastfeeding were fundamental to the acquisition of the pacifier habit and social levels and lower income can be considered predictors of inclusion of other forms of feeding, which is not natural. The results of evaluations of the stomatognathic system, it was possible to observe that there was no relationship between type and duration of breastfeeding and the studied functions, except between duration of breastfeeding and interdentalization (p=0,033). So, the type and duration of breastfeeding were not determining to the emergence of alterations in chewing, swallowing, and breathing functions, what suggests that these alterations have multifactorial causes.